Perceptions and attitudes of medical students regarding the coronavirus disease 2019 pandemic and relationships with personality traits and psychological resilience: COVID-19 and medical students - Yazla, Ece; Karakasli, Ahmet Alp; Aydinoglu , Unsal; Ozalp , Elvan (Journal of Surgery and Medicine, 2025)
Background/Aim: COVID-19 adversely affects mental health. We aimed to investigate COVID-19-related perceptions and attitudes in medical school students and to assess possible relationships with students’ psychological resilience levels and personality traits. Methods: This was a cross-sectional study carried out with 186 students in medical school at Hitit University Faculty of Medicine from March 18, 2021 to May 27, 2021. The sociodemographic form, perceptions and attitudes related to the COVID-19 pandemic, the Eysenck Personality Inventory (short form), and the Brief Psychological Resilience Scale were delivered to the students via mobile phone or e-mail and data were collected online. Results: In the COVID-19 perception scale, the assessment of dangerousness was found to be significantly higher among those living with at-risk individuals (P=0.026). In the perception of control subscale, personal control was found to be significantly higher in students who did not live with at-risk individuals (P=0.018). In the COVID-19 avoidance attitudes scale, behavioral avoidance was significantly more pronounced in students living with at-risk individuals (P=0.016). In our study, anxiety and depression were predominant in the brief symptom inventory. In the short form of the Eysenck Personality Inventory, it was observed that higher scores were obtained mostly in the neuroticism and extraversion dimensions. Conclusion: The findings of this study examining medical students show links between demographic factors, personality traits, and responses in the context of COVID-19 coping behaviors.